2013
DOI: 10.1530/eje-12-0718
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Proteomic biomarkers of type 2 diabetes mellitus risk in women with polycystic ovary syndrome

Abstract: Women with polycystic ovary syndrome (PCOS) are at increased risk of developing insulin resistance and type 2 diabetes mellitus (T2DM). In this study, we attempted to list the proteomic biomarkers of PCOS and T2DM that have been published in the literature so far. We identified eight common biomarkers that were differentially expressed in both women with PCOS and T2DM when compared with healthy controls. These include pyruvate kinase M1/M2, apolipoprotein A-I, albumin, peroxiredoxin 2, annexin A2, a-1-B-glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…Publications so far in this field have sampled various tissues in small numbers of women and proposed a panel of possible biomarkers. With plasma being the most easily accessible tissue, the early studies have shown altered expression of acute-phase response proteins and markers of inflammation (110,111). From omental adipose tissue, proteins related to intermediate metabolism, oxidative stress and differentiation have been described (111,112).…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…Publications so far in this field have sampled various tissues in small numbers of women and proposed a panel of possible biomarkers. With plasma being the most easily accessible tissue, the early studies have shown altered expression of acute-phase response proteins and markers of inflammation (110,111). From omental adipose tissue, proteins related to intermediate metabolism, oxidative stress and differentiation have been described (111,112).…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…Therefore, flotillin overexpression could induce the upregulation of EGFR signaling, thereby leading to disruption of cadherin-mediated intercellular adhesion. Reciprocally, cadherins also exert pro-oncogenic effects, notably in breast tumors, by participating in EGFR activation, either independent (Galazis et al, 2013). Overexpression of flotillins in tumors cells is associated with metastasis formation but the molecular mechanisms involved remain to be determined.…”
Section: Disease Relevance Of Flotillin-mediated Roles At Adhesionsmentioning
confidence: 99%
“…The increase in alpha-1-acid glycoprotein detected by ELISA and suggested by 2DE (although not reaching statistical significance after FDR) has been previously reported in obese adults [28] and T2DM [29], though its biological significance remains uncertain.…”
Section: Discussionmentioning
confidence: 92%